2012
DOI: 10.1093/geronb/gbs081
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Stressors, and Frailty Among Older Mexican American Adults

Abstract: Frailty has been hypothesized to reflect age-related physiological vulnerability to stressors, and the analyses presented indicate partial support for this hypothesis in an older sample of Mexican Americans. Future research needs to incorporate measures of stressors and social support in examining those who become frail, especially in minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 53 publications
8
71
3
1
Order By: Relevance
“…Group‐based trajectory modeling has been used to identify outcome patterns for disability at the end of life36; frailty,39 depression,40 and hypertension41 in general populations; and short‐term depression in young survivors of breast cancer 42, 43. To the best of our knowledge, the current study is the first application of this statistical method to long‐term outcomes in older breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Group‐based trajectory modeling has been used to identify outcome patterns for disability at the end of life36; frailty,39 depression,40 and hypertension41 in general populations; and short‐term depression in young survivors of breast cancer 42, 43. To the best of our knowledge, the current study is the first application of this statistical method to long‐term outcomes in older breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In the Women's Health and Aging Studies (which also used Fried's criteria), the odds of frailty were increased for those of low education or income regardless of race . The Hispanic Established Populations for the Epidemiologic Study of the Elderly (which used Fried's criteria) found that financial strain was related to increases in frailty over time . The Hertfordshire Cohort Study highlighted socioeconomic inequalities in frailty using Fried's criteria .…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, the population under study is viewed as a mixture within which a finite number of subgroups (latent classes) can be identified possessing distinct trajectory shapes. Each trajectory is then modeled with its own functional form (e.g., linear, quadratic) and direction simultaneously [5457]. These models were developed using the user-written Stata procedure for trajectory modeling [53] based on semi-parametric, finite mixture modeling using maximum likelihood.…”
Section: Methodsmentioning
confidence: 99%